Elemen Budaya Melayu pada Rumah Tjong A Fie di Medan - Rudiansyah . (JURNAL RUPA, 2019)
‘The elements of Malay cultural at Tjong A Fie’s house in Medan’ is selected as the title of the article with the purpose of assessing and understanding the acculturation that was discovered on the buildings with Chinese style in Medan City. This research was focused on the objects of Tjong A Fie’s house. This research used John W. Berry’s acculturation theory; while the method that is used is the qualitative descriptive method. An acculturation is a prosess that happens when one group of people with some kind of culture confronts the elements of some other culture. From this comes into being the change of the origin cultures, yet these two cultures have not lost the elements of their own cultures. The acculturation can be seen on part of Tjong A Fie’s house like the gold color that was used dominatedly, the pictures on the cloth and the Malay special window shapes.